Development of an immunochromatographic assay for the detection of alternariol in cereal and fruit juice samples. Issue 6 (2nd November 2017) - Kong, Dezhao; Xie, Zhengjun; Liu, Liqiang; Song, Shanshan; Zheng, Qiankun; Kuang, Hua
ABSTRACT: An immunochromatographic strip was developed for the determination of alternariol( AOH) using both semi-quantitative and quantitative methods based on a sensitive monoclonal antibody we produced. With AOH-spiked samples, the visual limit of detection for cereal and juice were 160 ng/g and 25 ng/mL, and the cut-off values were 640 ng/g and 100 ng/mL, respectively. For quantitative analysis based on a strip scan reader, the calculated limit of detection was 15.5–19.4 ng/g for cereal and 2.8–3.5 ng/mL for fruit juice. The recovery rates ranged from 116% to 125%, and 113% to 123%, respectively. Therefore, this method was effective for AOH detection and suitable for on-site detection and rapid screening of samples.